New composites of polydopamine-coated bridged Polysilsesquioxane and Pd Nanoparticles Containing POSS. (13th June 2019) - Oh, Sinseok; Kang, Pil-seon; Lee, Yongpyo; Lee, Jae-Ik; Park, No-Hyung; Lim, Jung-Hyurk; Kim, Kyung-Min
Abstract: Spherical bridged polysilsesquioxane (BPS) nanoparticles were prepared by the hydrolysis and condensation reaction of urethane-based BPS monomer made from 1, 4-butanediol and 3-(triethoxysily)propyl isocyanate. Polydopamine (PDA) was coated on the surfaces of BPS by the self-polymerization of dopamine under pure oxygen at room temperature. To create aggregates of Pd nanoparticles on PDA-coated BPS, polyhedral oligomeric silsesquioxane (POSS-NH3 + ) as a cross-linker was incorporated on the surfaces of PDA-coated BPS. Aggregates of Pd nanoparticles were densely produced on the surfaces of PDA-coated BPS by the mixing of POSS/PDA-coated BPS and palladium (Π) acetate in a methanol solution.